2020
DOI: 10.1021/acs.inorgchem.0c02611
|View full text |Cite
|
Sign up to set email alerts
|

Composition–Thermometric Properties Correlations in Homodinuclear Eu3+ Luminescent Complexes

Abstract: A family of homodinuclear Ln 3+ (Ln 3+ = Gd 3+ , Eu 3+ ) luminescent complexes with the general formula [Ln 2 (β-diketonato) 6 ( N -oxide) y ] has been developed to study the effect of the β-diketonato and N -oxide ligands on their thermometric properties. The investigated complexes are [Ln … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…The 5 D 0 → 7 F 2 transitions depict a significant hypersensitivity, which is commonly reported for europium 𝛽‐diketonato complexes (Figure S20a–d). 57 The shape of the 5 D 0 → 7 F 2 transition is similar for the species [( S/R )‐1] and [( S , R )‐3] , or [( S , S , S/R , R , R )‐2] and [( S , S , S/R , R , R )‐4] . Nevertheless the ratio R of the intensities of the transition 5 D 0 → 7 F 2 and 5 D 0 → 7 F 1 (R = I( 5 D 0 → 7 F 2 )/I( 5 D 0 → 7 F 1 )) is found close for all the compounds, that is, 23.0 for [( S/R )‐1] , 21.8 for [( S , S , S/R , R , R )‐2] , 20.6 for [( S , R )‐3] , and 20.2 for [( S , S , S/R , R , R )‐4] , highlighting a similar symmetry of the Eu(III) site in the compound series.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The 5 D 0 → 7 F 2 transitions depict a significant hypersensitivity, which is commonly reported for europium 𝛽‐diketonato complexes (Figure S20a–d). 57 The shape of the 5 D 0 → 7 F 2 transition is similar for the species [( S/R )‐1] and [( S , R )‐3] , or [( S , S , S/R , R , R )‐2] and [( S , S , S/R , R , R )‐4] . Nevertheless the ratio R of the intensities of the transition 5 D 0 → 7 F 2 and 5 D 0 → 7 F 1 (R = I( 5 D 0 → 7 F 2 )/I( 5 D 0 → 7 F 1 )) is found close for all the compounds, that is, 23.0 for [( S/R )‐1] , 21.8 for [( S , S , S/R , R , R )‐2] , 20.6 for [( S , R )‐3] , and 20.2 for [( S , S , S/R , R , R )‐4] , highlighting a similar symmetry of the Eu(III) site in the compound series.…”
Section: Resultsmentioning
confidence: 94%
“…7 F 2 transitions depict a significant hypersensitivity, which is commonly reported for europium β-diketonato complexes (Figure S20a-d). 57 The shape of the 5 It is worth noticing that a value of R > 10 is commonly observed for Eu(III) β-diketonate complexes. [58][59][60][61][62][63] The emission decay curves can be fitted by monoexponential functions (Figure S21) confirming the presence of single spectroscopic Eu(III) site and thus supporting the existence of single monomeric species in solution.…”
Section: Luminescence and Cpl Measurementsmentioning
confidence: 99%
“…In our previous work, we showed that heterocyclic N -oxide ligands such as pyrazine N -oxide or 4,4′-bipyridine N -oxide (bipyMO) react with neutral lanthanide tris-β-diketonato Eu­(β-diketonate) 3 fragments stabilizing homodinuclear molecular compounds Eu 2 (β-diketonate) 6 ( N -oxide) y (β-diketonate = thenoyltrifluoroacetonate, dibenzoylmethanate, benzoyltrifluoroacetonate, or hexafluoroacetylacetonate; y = 2 or 3). Heterotopic ligands in these molecular compounds behave as O donor bridging and hypodentate ligands maintaining an uncoordinated nitrogen donor functionality. Luminescence studies have established the effect of the β-diketonato and N -oxide ligands on the thermometric properties of the obtained compounds, which are determined by the presence of two nonradiative deactivation channels, back energy transfer from Eu 3+ to the ligand triplet levels and ligand to metal charge transfer (LMCT), the latter being strongly influenced by the N -oxide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…6a ). 107 These dinuclear Eu( iii ) complexes exhibited efficient photosensitized emission properties and effective temperature-dependent emission intensity changes, originating from both ligand-to-metal charge transfer (LMCT) and localized ligand T 1 quenching sites.…”
Section: Photophysics Of Eu( III ) Complexes With ...mentioning
confidence: 99%